La congestión vehicular y su incidencia en la demanda turistica del cantón Jujan - Rodriguez Holguin, Darling Otton (2021)
The present project on traffic congestion and its incidence on tourist demand in the canton of Jujan, is developed with the aim of indicating the incidence of such an evento on the turist demand of the place, identifying in such a way the factors that cause it, the frequency with which it occurs and other aspects that revolve around that situation. The problema of traffic congestion has been evident for years, so more and more people who have experienced the inconvenience of being stuck in traffic do not consider the canton as an option to visit during leisure time, go there to eat or tour the tourist places of the site, because the Access roads are the scene of a difficult situation with regard to vehicle traffic and it is something that the tourists prefer to avoid. For this reason, this research emphasizes the importance of the infrastructure of a tourist destination to recibe visitors, so a survey was conducted to obtain information from direct sources, from which this information was analyzed, which indicates that this problema has a strong incidence on tourism demand in the canton of Jujan, so solutions that can be effective in dealing with traffic congestion are proposed.